2019
DOI: 10.3389/fmicb.2019.01015
|View full text |Cite
|
Sign up to set email alerts
|

Leaf and Root Endospheres Harbor Lower Fungal Diversity and Less Complex Fungal Co-occurrence Patterns Than Rhizosphere

Abstract: Plant-associated microbiomes are key determinants of host-plant fitness, productivity, and function. However, compared to bacterial community, we still lack fundamental knowledge concerning the variation in the fungal microbiome at the plant niche level. In this study, we quantified the fungal communities in the rhizosphere soil, as well as leaf and root endosphere compartments of a subtropical island shrub, Mussaenda kwangtungensis , using high-throughput DNA sequencing. We found that f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 108 publications
7
36
0
Order By: Relevance
“…Belowground habitats also had a greater proportion of Basidiomycota reads, specifically Agaricomycetes. These broad taxonomic patterns among different plant-associated habitats resemble those found in other temperate tree species such as Magnolia kwangtungensis (Qian et al, 2019), Populus trichocarpa and P. deltoides × P. trichocarpa hybrids (Cregger et al, 2018), and Picea abies (Kovalchuk et al, 2018;Ren et al, 2019;Terhonen et al, 2019), suggesting that, at higher taxonomic levels, microbiomes are fairly consistent among tree species. However, as our study and others show, at more specific taxonomic levels, microbiomes diverge among closely related host species (Cregger et al, 2018;Rogers et al, 2018) and even among different genotypes of the same host species (Bálint et al, 2013;Veach et al, 2019).…”
Section: Discussionsupporting
confidence: 65%
“…Belowground habitats also had a greater proportion of Basidiomycota reads, specifically Agaricomycetes. These broad taxonomic patterns among different plant-associated habitats resemble those found in other temperate tree species such as Magnolia kwangtungensis (Qian et al, 2019), Populus trichocarpa and P. deltoides × P. trichocarpa hybrids (Cregger et al, 2018), and Picea abies (Kovalchuk et al, 2018;Ren et al, 2019;Terhonen et al, 2019), suggesting that, at higher taxonomic levels, microbiomes are fairly consistent among tree species. However, as our study and others show, at more specific taxonomic levels, microbiomes diverge among closely related host species (Cregger et al, 2018;Rogers et al, 2018) and even among different genotypes of the same host species (Bálint et al, 2013;Veach et al, 2019).…”
Section: Discussionsupporting
confidence: 65%
“…However, the ecological effects of these soil amendments on strawberry cultivation needs a comprehensive evaluation, including the determination of strawberry growth, production and quality in different treatments, and even its long-term effects [10,68]. At the same time, we will consider the response of a broader range of soils with different physicochemical properties, climate types and field management practices to soil amendments [7,69]. EM and BS based studies have revealed the effects of soil amendments on bacterial community structure and symbiotic network in strawberry soil.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the possible changes caused by biochar incorporation and/or the durum genotype to the soil microbiome, we specifically focused on the rhizosphere, which is the interface between plant roots and soil, since the microorganisms colonizing the rhizosphere may contribute to plant growth and health (Richter-Heitmann et al, 2016); moreover, different studies have already established that the rhizosphere corresponds to the plant-soil compartment harboring a higher richness (Qian et al, 2019).…”
Section: Biochar Treatment But Not Durum Wheat Genotype Has a Signifimentioning
confidence: 99%